An exhaustive experimental study of a novel air-water based thermoelectric cooling unit. (1st November 2016) - Sadighi Dizaji, Hamed; Jafarmadar, Samad; Khalilarya, Shahram; Moosavi, Amin
Highlights: A novel air-water based thermoelectric cooling unit is experimentally investigated. Different climate conditions are simulated using of different air flow rates and temperatures. Various parameters are evaluated to find optimum condition. COP/COPmax is studied as a new consideration and memorable behavior was observed. Abstract: In this paper, the cooling feasibility of air flow via a novel air-water based TEC system (as an alternative air cooling unit) is experimentally investigated for different climate conditions. Contrary to previous studies, thermoelectric hot side temperature was adjusted by a low constant water flow rate (and not by an air fan) which significantly increased the cold side performance of TEM. Ten parameters including Ta, inlet, Tw, inlet, Ta, outlet, Tw, outlet, Tc, Ta, m ̇ a, m ̇ w and DC voltage and DC current were directly recorded by measurement instruments during the experiments. Six other parameters including qc, qh, COPc, COPmax, COPc /COPmax and qair were evaluated by formulas and correlations using of aforesaid measured data. Five numbers of aforementioned parameters were variant parameters. Indeed, the effect of m ̇ a, m ̇ w, DC voltage/current and Ta, inlet (variant parameters) on other impressionable parameters were investigated in present study. Optimum working condition was evaluated from a new point of view. Indeed, in this paper, it was accidently found out that, despite the descending behavior of both COPc and COPmax (due to changing of variants), the ratio of said parameters (COPc /COPmax ) creates a peak point (ascending and then descending) in all cases. Said peak point can be considered as an appropriate working condition of thermoelectric units. Findings showed that, the cold side of thermoelectric system can act as an applicable air cooling system especially when the hot side of thermoelectric is cooled by a current liquid such as water.